Subjectivity “Demystified”: Neurobiology, Evolution, and the Explanatory Gap - Feinberg, Todd E.; Mallatt, Jon (Frontiers in Psychology, 2019)
While life in general can be explained by the mechanisms of physics, chemistry and biology, to many scientists and philosophers it appears that when it comes to explaining consciousness, there is what the philosopher Joseph Levine called an “explanatory gap” between the physical brain and subjective experiences. Here we deduce the living and neural features behind primary consciousness within a naturalistic biological framework, identify which animal taxa have these features (the vertebrates, arthropods, and cephalopod molluscs), then reconstruct when consciousness first evolved and consider its adaptive value. We theorize that consciousness is based on all the complex system features of life, plus the even more complex features of elaborate brains. We argue that the main reason why the explanatory gap between the brain and experience has been so refractory to scientific explanation is that it arises from both life and from varied and diverse brains and brain regions, so bridging the gap requires a complex, multifactorial account that includes the great diversity of consciousness, its personal nature that stems from embodied life, and the special neural features that make consciousness unique in nature.